Elucidating the impact of boron fertilization on soil physico-chemical and biological entities under cauliflower-cowpea-okra cropping system in an Eastern Himalayan acidic Inceptisol - Bhupenchandra, Ingudam; Basumatary, Anjali; Choudhary, Anil K.; Kumar, Adarsh; Sarkar, Dibyendu; Chongtham, Sunil Kumar; Singh, Athokpam Herojit; Devi, Elangbam Lamalakshmi; Bora, S. S.; Salam, Menaka Devi; Sahoo, Manas Ranjan; Gudade, Bharat A.; et al. (Frontiers in Microbiology, 2022)
Information on the role of boron (B) on soil physico-chemical and biological entities is scarce, and the precise mechanism in soil is still obscure. Present field investigation aimed to assessing the implication of direct and residual effect of graded levels of applied-B on soil biological entities and its concomitant impact on crop productivity. The treatments comprised of five graded levels of B with four replications. To assess the direct effect of B-fertilization, cauliflower was grown as a test crop wherein, B-fertilization was done every year. Further, assessment of succeeding residual effects of B-fertilization, cowpea and okra were grown as test crops and, B-fertilization was phased out in both crops. The 100% recommended dose of NPK (RDF) along with FYM was uniformly applied to all crops under CCOCS. Results indicated that the direct effect of B had the edge over residual effect of B in affecting soil physico-chemical and biological entities under CCOCS. Amongst the graded levels of B, application of the highest B level (2 kg ha-1) was most prominent in augmenting microbiological pools in soil at different crop growth stages. The order of B treatments in respect of MBC, MBN, and soil respiration at different crop growth stages was 2.0 kg B ha-1>1.5 kg B ha-1>1.0 kg B ha-1>0.5 kg B ha-1>0 kg B ha-1, respectively. Moreover, maximum recoveries of PMS and PMN were noticed under 2 kg B ha-1. Analogous trend was recorded in soil microbial populations at different crop growth stages. Similarly, escalating B levels up to 2 kg B ha-1 exhibited significantly greater soil enzymatic activities viz., arylsulphatase (AS), dehydrogenase (DH), fluorescein diacetate (FDA) and phosphomonoesterase (PMA), except urease enzyme (UE) which showed an antagonistic effect of applied-B in soil. Greater geometric mean enzyme activity (GMEA) and soil functional diversity index were recorded under 2 kg B ha-1 in CCOCS, at all crop growth stages over control. The inclusive results indicated that different soil physico-chemical and biological properties CCOCS can be invariably improved by the application of graded levels of B up to 2 kg B ha-1 in an acid Inceptisol.